"HUBUNGAN SELF-EFFICACY DENGAN PERILAKU PROSOSIAL SISWA SMP NEGERI 44 BANDUNG PADA MASA PANDEMI COVID-19" - Syahida Karim, - (2021)
ABSTRAC This study aims to determine the correlation between self-efficacy and prosocial behavior of students at 44 Junior High School Bandung during the Covid-19 pandemic. The epidemic that is currently infecting many countries has caused changes in various systems of human life, one of the systems that has affected is education. The education system in Indonesia has turned online. This causes the students lack of socialization to the surrounding environment and the self-efficacy of students is affected by the pandemic. This study has a sample of 249 students using the technique Proportional Stratified Random Sampling. The instrument used is the General Self- Efficacy Scale by Ralf Schwarzer and Matthias Jerusalem as many as 9 items as well as prosocial behavior instruments developed from the theory of Mussen et al, amounting to 13 items after the validity & reliability test process. The statistical method used to determine the correlation of two variables is the Kendall tau technique. That is because the data are not normally distributed, so according to Sugiyono, the Kendall tau correlation is very suitable to be used. With the level of self-efficacy in the low category and prosocial behavior in the same level. The result of correlation coefficient proves that there is a highly significant correlation and positive category between self-efficacy and prosocial behavior of students 44 Junior High School Bandung during the Covid-19 pandemic. Proving that the lower level of self-efficacy will be accompanied by lower level of prosocial behavior. Keyword: (1) Self-Efficacy, (2) Prosocial Behavior, (3) Pandemic Covid-19.